ASITA 2010 e l'importanza dell'informazione Geografica - Leonardi, Sandra (GEOmedia, 2010)
ASITA 2010 Flood in north-east, securing the 'locomotive of Italy'. Irreversible collapse, due to heavy rains and lack of proper management of funds allocated and weighted. Cranes and rooftops are occupied by protesters demanding the right to work, the right to education, the right to know the truth about the unsolved mysteries. The economic crisis keeps stalling the country. This is the scenario in which took place the 14th Conference of ASITA (Brescia - 9 / 12 November 2010), whose themes concern all aspects of local knowledge at the service of citizens and whose presenters, technicians, researchers could avoid some environmental disasters, economic geology, and then that beset the peninsula, if only there were a true disclosure of geographic information.